https://iejee.com/index.php/IEJEE/article/view/152/149 - Sibel Yoleri (International Electronic Journal of Elementary Education, 2016)
The aim of this study was to determine how children’s temperament and language skills predict the effects of teacher–child relationships in preschool. Parents and preschool teachers completed three questionnaires: The Student-Teacher Relationship Scale, the Marmara Development Scale and the Short Temperament Scale for Children. The relational survey method was used in this study. The sample consisted of 195 preschool children. According to the results, a negative significant relationship was found between the teacher-child relationships scores and the reactivity sub-dimension of temperament. Also, there are positive significant relationships between teacher-child relationship scores and language skills. In addition, both the reactivity sub dimension of temperament and language skills demonstrate a predictor effect on the teacher-child relationships. Reactivity was the most important temperament trait factor affecting relationships.